Impact of sex on diabetic nephropathy and the renal transcriptome in UNx db/db C57BLKS mice. Issue 24 (25th December 2019) - Sembach, Frederikke E.; Fink, Lisbeth N.; Johansen, Thea; Boland, Brandon B.; Secher, Thomas; Thrane, Sebastian T.; Nielsen, Jens C.; Fosgerau, Keld; Vrang, Niels; Jelsing, Jacob; Pedersen, Tanja X.; Østergaard, Mette V.
Abstract: Diabetic nephropathy (DN) is associated with albuminuria and loss of kidney function and is the leading cause of end‐stage renal disease. Despite evidence of sex‐associated differences in the progression of DN in human patients, male mice are predominantly being used in preclinical DN research and drug development. Here, we compared renal changes in male and female uninephrectomized (UNx) db/db C57BLKS mice using immunohistochemistry and RNA sequencing. Male and female UNx db/db mice showed similar progression of type 2 diabetes, as assessed by obesity, hyperglycemia, and HbA1c. Progression of DN was also similar between sexes as assessed by kidney and glomerular hypertrophy as well as urine albumin‐to‐creatinine ratio being increased in UNx db/db compared with control mice. In contrast, kidney collagen III and glomerular collagen IV were increased only in female UNx db/db as compared with respective control mice but showed a similar tendency in male UNx db/db mice. Comparison of renal cortex transcriptomes by RNA sequencing revealed 66 genes differentially expressed ( p  < .01) in male versus female UNx db/db mice, of which 9 genes were located on the sex chromosomes. In conclusion, male and female UNx db/db mice developed similar hallmarks of DN pathology, suggesting no or weak sex differences in the functional and structural changes during DN progression. Abstract : Despite evidence of sex‐associated differences in the progression of DN in human patients, male mice are predominantly being used in preclinical DN research and drug development. Here, we compared renal changes in male and female uninephrectomized (UNx) db/db C57BLKS mice. We find that male and female UNx db/db mice developed similar hallmarks of DN pathology.